Assessment of interbreeding and introgression of farm genes into a small Scottish Atlantic salmon Salmo salar stock: ad hoc samples – ad hoc results?. Issue 6 (12th October 2016) - Verspoor, E.; Knox, D.; Marshall, S.
Abstract : An eclectic set of tissues and existing data, including purposely collected samples, spanning 1997–2006, was used in an ad hoc assessment of hybridization and introgression of farmed wild Atlantic salmon Salmo salar in the small Loch na Thull (LnT) catchment in north‐west Scotland. The catchment is in an area of marine farm production and contains freshwater smolt rearing cages. The LnT S. salar stock was found to be genetically distinctive from stocks in neighbouring rivers and, despite regular reports of feral farm S. salar, there was no evidence of physical or genetic mixing. This cannot be completely ruled out, however, and low level mixing with other local wild stocks has been suggested. The LnT population appeared underpinned by relatively smaller effective number of breeders ( N eb ) and showed relatively low levels of genetic diversity, consistent with a small effective population size. Small sample sizes, an incomplete farm baseline and the use of non‐diagnostic molecular markers, constrain the power of the analysis but the findings strongly support the LnT catchment having a genetically distinct wild S. salar population little affected by interbreeding with feral farm escapes.